The randomized study of enteral nutrition with rapid versus conventional administration in acute stroke patients; the protocol of rapid EN trial - Suzuki, Kentaro; Onodera, Hidetaka; Sugiyama, Rie; Okubo, Seiji; Kimura, Naoto; Kaku, Shogo; Seki, Rieko; Fujita, Satoshi; Nomura, Koichi; Takagiwa, Taiki; Katafuchi, Izumi; Nakamura, Homare; et al. (Frontiers in Neurology, 2024)
RATIONALE: Enteral nutrition is beneficial for stroke patients with oral intake difficulties. However, it is time consuming and may interfere with routine medical care. Therefore, there is a clinical benefit if enteral nutrition can be safely administered in a short time. Although our retrospective study showed the safety of rapid administration, it remains unclear whether rapid administration of enteral nutrition is as safe as conventional administration. AIM: The randomized study of Enteral Nutrition with Rapid versus conventional administration in acute stroke patients (Rapid EN trial) aims to clarify the safety of rapid feeding of enteral nutrition compared with conventional feeding. METHODS AND DESIGN: This is an investigator-initiated, multicenter, prospective, randomized, open-label, blinded end-point clinical trial. Eligible criteria include acute stroke patients who have difficulty with oral intake defined as severe altered consciousness (Japan Coma Scale 10-300) or modified water swallowing test < 4. The target enrollment is 700 patients, with 350 patients receiving rapid enteral nutrition at a rate of 100 ml in 5 minutes (Rapid EN group) and 350 patients receiving conventional enteral nutrition at a rate of 100 ml in 30 minutes (Conventional EN group). STUDY OUTCOME: The primary outcome is the incidence of one or more complications of vomiting or diarrhea or pneumonia within 7 days would be non-inferior in the rapid EN group compared to the conventional EN group. Secondary outcomes were total time spent on enteral nutrition within 7 days from enteral nutrition, the incidence of vomiting, diarrhea and pneumonia within 3 or 7 days, and the rate of favorable clinical outcome. DISCUSSION: Since no previous reports have focused on the speed of administration, we felt it was necessary to prove the safety of rapid administration. If this study shows positive results, it will not only benefit patients, but also reduce the burden of medical care. We believe this study is novel and will be useful in clinical practice. TRIAL REGISTRATION: UMIN000046610